2011
DOI: 10.1186/1471-2296-12-138
|View full text |Cite
|
Sign up to set email alerts
|

Identifying context factors explaining physician's low performance in communication assessment: an explorative study in general practice

Abstract: BackgroundCommunication is a key competence for health care professionals. Analysis of registrar and GP communication performance in daily practice, however, suggests a suboptimal application of communication skills. The influence of context factors could reveal why communication performance levels, on average, do not appear adequate. The context of daily practice may require different skills or specific ways of handling these skills, whereas communication skills are mostly treated as generic. So far no empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 37 publications
6
34
0
2
Order By: Relevance
“…Thus, GPs seemed to tailor their reassurance to the context of that specific consultation, which explains why they described such a wide variety of strategies. The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38].…”
Section: Discussionsupporting
confidence: 84%
“…Thus, GPs seemed to tailor their reassurance to the context of that specific consultation, which explains why they described such a wide variety of strategies. The context-specific and goal-directed character of doctor-patient communication has also been shown in previous research [27,40,41]. The situation-specificity of reassurance has also been demonstrated in our study exploring the patients’ perspective on reassurance, which showed that what is experienced as reassuring by patients largely depends on their specific worrying cognitions [38].…”
Section: Discussionsupporting
confidence: 84%
“…Trainees' reflections on situations during which the skills they have learned during medical training are ineffective, again underline that the context-specific nature of medical communication in daily practice should not be ignored [27][28][29][30]. In line with previous studies, there seems to be a need for more tailored, context-specific communication strategies that are adaptable to specific situations [31,32].…”
Section: Main Findings In Relation To the Literaturementioning
confidence: 62%
“…In order to learn from their experiences, the need for debriefing and for discussion throughout the clerkships seems high, considering the impact of this form of learning (Egnew & Wilson 2011) and contextual influences on communication (Bensing et al 2003, Essers et al 2011. However, in a recent study, Wouda and van de Wiel (2012) found that there is no substantial increase in student communication levels from clerkships.…”
Section: Discussionmentioning
confidence: 91%
“…Recent literature shows that such context factors influence communication patterns (MacDonald & Green 2001;Bensing et al 2003;Hawken 2005;Yamkovenko & Holton 2010;Essers et al 2011). Although students value patient centredness and want to learn about Practice points .…”
Section: Introductionmentioning
confidence: 97%